PHYTOPLANKTON COMPOSITION IN THE FLUVIAL-LAGOON SYSTEMS POM-ATASTA AND PALIZADA DEL ESTE, ADJACENT TO THE TERMINOS LAGOON CAMPECHE, MÉXICO - Rocio Elizabeth Muciño Marquez; María Guadalupe Figueroa Torres; Arturo Aguirre León (Acta Biológica Colombiana, 2014)
ABSTRACT The composition and abundance of phytoplankton community, and its relation to physical and chemical factors was evaluated in the fluvial-lagoon systems Pom-Atasta (PA) and Palizada del Este (PE), in February, 2011. Water samples were collected in ten sampling sites in each lagoon, with a van Dorn bottle at the surface and in the middle of the water column to measure temperature, salinity, dissolved oxygen, inorganic nutrients, chlorophyll a and the composition and abundance of phytoplankton. In order to describe the behavior of phytoplankton it was calculated species abundance, Shannon-Wiener diversity and Pielou equitability indices were used, and to analyze the relationship between the abundance of phytoplankton species and environmental variables, a canonical correspondence analysis (CCA) was applied. The results showed that PE was the lagoon that presented a great biodiversity with 348 identified taxa, maximum abundance values (269 × 103 cells L-1), H’ (3.2) and J’ (0.95). Cylindrotheca closterium was the most abundant species in both systems, observing the highest abundance (52.5 × 103 célls L-1) in PA, forming incipient toxic algal blooms. It should be noted that salinity was the most influential environmental variable in the composition and abundance of phytoplankton.